A New Paradigm for Solid Waste Management in Integrated Waste Management Site Piyungan Yogyakarta, Indonesia - Budiman, Arief; Prihandoko, Diananto; Fandeli, Chafid; Setyono, Prabang (Applied Mechanics and Materials, 2020)
The implementation of the waste management technology in Integrated Waste Management Site, in Bahasa: Tempat Pengolahan Sampah Terpadu (TPST) Piyungan of the Special Region of Yogyakarta Indonesia has not been optimal and it has negative impact, especially on environment and surrounding community. TPST Piyungan has both positive impact of opening employment for waste pickers as well as negative impact of pollution in surrounding environment. Increasing of solid waste input is not balanced with the processing rate. Concerning with the aforementioned background the study aimed at studying the people perception of waste management in the TPST Piyungan and formulating a new paradigm for solid waste management in TPST Piyungan by proposing a waste-to-energy technology that able to solve the existing problems and become a business-centered activity instead of cost-centered, or in short term waste-entrepreneurship (wastepreneurship). The study was conducted in TPST Piyungan and surroundings villages as samples. The study used quantitative analysis method. People perception were collected using questionnaires distributed to 30 respondents in nearby villages. Proposed technology was selected using Green Quality Function Deployment (GQFD) and Less Objective Criteria (LOC). Economic evaluation parameters are Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period. The results of the study showed that 70% of the villagers accepted the presence of the advanced waste management in the TPST Piyungan. The results of GQFD and LOC showed that incinerator was the selected technology. The results of economic showed that incinerator was economically feasible with the NPV of IDR 86.09 billion, the IRR of 13.35%, and the net profit margin in the range of 6.89 – 18.79% in the operational period of 18 years, and the static payback period of 7 years. Therefore, the implementation of wastepreneurship in form of social, economic, technical and environment is highly potential.